There Goes the Neighborhood? The Local Impacts of State Policies That Override Municipal Zoning - Hector Blanco; Noémie Sportiche (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Prior research shows that restrictive zoning regulations are major drivers of rising housing costs and residential segregation in the United States. In response, a growing number of state and local governments are passing laws to allow for denser housing in strictly zoned localities, despite entrenched opposition from incumbent residents. This paper examines whether incumbent residents' responses undermine the success of these policies by studying new construction permitted under Massachusetts Chapter 40B; one of the longest-standing and most productive examples of a housing policy that bypasses local zoning laws. Exploiting hyperlocal variation in residents' proximity to new 40B buildings, we find that only a subset of larger 40B developments cause property values to decrease, and that this effect is both highly localized and only emerges in the longer term, many years after these developments are proposed. Focusing on these larger developments that are more likely to elicit resident reactions, we find that only a fraction of incumbent residents move out after their approval and that the magnitude of these migration responses is insufficient to undermine policymakers' desegregation goals. We also do not find evidence that incumbent residents become more politically active against future development, as they are no more likely to vote in local or general elections nor are they more likely to vote for repealing Chapter 40B after 40B developments are proposed near their homes.
Keywords: R52; R23; R28; 330; zoning; housing prices; migration; political participation